2020
DOI: 10.1021/acs.joc.9b02718
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine-Based Self-Assembly as an Enantioselective Catalyst Scaffold

Abstract: A self-assembled G-quadruplex formed by guanosine and borate as the chiral scaffold was used to catalyze the asymmetric Friedel–Crafts reaction in water. Catalysis, depending on the self-assembly of guanosine and borate into a fibrillar structure in the presence of Cu2+ ions, can be modulated by the assembly concentration, temperature, and amount of Cu2+ ions. Detailed spectral experiments proved that the guanosine-based assembly in solution was responsible for the enantioselective catalysis, rather than small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The incorporation of G-quartet structures into supramolecular assemblies opens the possibility for nucleopeptides to be supramolecular catalysts. As other recent examples of guanine-based supramolecular structures have been shown to catalyze peroxidase reactions in the presence of hemin [35] and have provided a chiral scaffold for enantiomeric Freidel-Crafts alkylation [36], guanosine containing nucleopeptides should also be tested for emergent catalytic properties. Additionally, as the mutualism between nucleic acids and peptides in biological systems has positioned nucleopeptides [37] and co-assemblies of peptides and nucleic acids [38,39] as important systems in understanding chemical evolution, the self-assembled guanosine containing nucleopeptides reported in this study may inform future studies of dynamic chemical networks.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of G-quartet structures into supramolecular assemblies opens the possibility for nucleopeptides to be supramolecular catalysts. As other recent examples of guanine-based supramolecular structures have been shown to catalyze peroxidase reactions in the presence of hemin [35] and have provided a chiral scaffold for enantiomeric Freidel-Crafts alkylation [36], guanosine containing nucleopeptides should also be tested for emergent catalytic properties. Additionally, as the mutualism between nucleic acids and peptides in biological systems has positioned nucleopeptides [37] and co-assemblies of peptides and nucleic acids [38,39] as important systems in understanding chemical evolution, the self-assembled guanosine containing nucleopeptides reported in this study may inform future studies of dynamic chemical networks.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels of Fmoc-Glu and dG/dA upon addition of K + ions It was known that guanosine based derivatives self-associated into G-quadruplexes , which were composed with an arrangement of four guanine moieties connected together by eight hydrogenbonding interactions and stabilized by K + ions, and then the Gquartets stacked to form stable G-quadruplexes (G 4 ). 34,[44][45][46][47][48][49][50] However, it has been demonstrated that high-order aggregates for adenosine or deoxyadenosine upon addition of any alkali metal were unable to form. 49 Thus the K + ions were introduced into the system of Fmoc-Glu/dG and Fmoc-Glu/dA co-gels.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…At the end of this chapter, it is worth mentioning a few more non-obvious approaches to the asymmetric Friedel-Crafts reaction. They are for sure the use of N-heterocyclic carbenes as catalysts in the synthesis of indole-fused polycyclic alcohols [56], guanosinebased self-assembly as catalytic system [57], and various DNA-employing catalytic systems [58][59][60].…”
Section: Asymmetric Friedel-crafts Reactionsmentioning
confidence: 99%